Do Auditor Characteristics Lead to Tax Avoidance? - Amalia, Diah; Aritonang, Agustinus Lambas Cardo (Global Writing Academica Researching and Publishing, 2024)
This research aims to examine the influence of audit fees, audit tenure, and audit opinions on tax avoidance, with firm size, leverage, and profitability as control variables. The study focuses on companies in the financial sector listed on the Indonesia Stock Exchange (IDX) during the 2015-2021 observation period. The sample selection technique used is purposive sampling, resulting in a sample of 41 companies with 287 data points. Eviews 12 is utilized in this quantitative study. The research results indicate that audit fees, audit tenure, and audit opinions do not significantly influence tax avoidance. The implications of this research highlight the importance of tax planning for companies.